Export performance and direction of major agricultural commodities from Tamil Nadu - Ramalakshmi, G; Velavan, C; Muralidharan, C; Premavathi, R; Prahadeeswaran, M (Plant Science Today, 2025)
Tamil Nadu is India's second-largest economy and its agricultural performance is also significant. The state has been involved in trading of agricultural commodities for many years. In recent years, due to change in export policy of major commodities, it is necessary to measure the performance and direction at state level. Hence, the present study aims to analyze the trends and direction of the trade for selected agricultural commodities from Tamil Nadu. Port-wise export data of the major agricultural commodities from Tamil Nadu were used to assess the export dynamics during 2007-2022. Non-basmati rice, pulses and groundnut were selected for the study based on their significance in the state agriculture as well as in the export trade. The results of the study revealed that the export growth of pulses was the highest among the selected commodities with 21.8% and 28.1% in terms of quantity and value respectively followed by non-basmati with 16.27% and 20.1% in quantity and value terms respectively. However, the growth rate of export quantity of groundnut was negative with -0.1% whereas export value growth was positive with 5.9%. This revealed that export performance of pulses and non-basmati rice was better than groundnut. The Direction of export analysis revealed that Bangladesh and Benin for non-basmati rice, Sri Lanka, China and Singapore for pulses and Sri Lanka and Singapore for Groundnut would be the stable market for export from Tamil Nadu.